The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1037/emo0001122
|View full text |Cite
|
Sign up to set email alerts
|

I feel you: Prepandemic physiological synchrony and emotional contagion during COVID-19.

Abstract: The COVID-19 pandemic has a major impact on mental well-being and interpersonal relationships. Nonetheless, little is known about the complex interactions between one's overall perceived interpersonal closeness and physiological or psychological aspects of interpersonal functioning. This study aimed to understand the interaction between perceived interpersonal closeness during COVID-19 and interpersonal mechanisms in predicting well-being. We focused on two interpersonal mechanisms, one physiological and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Furthermore, emotional contagion goes beyond mere mimicry. It involves a deeper level of self-involvement, where individuals share feelings with others, even for brief moments, strengthening their emotional connection ( Mariadhas, 2019 ; Mayo et al, 2023 ). This shared emotional experience can have great effects on individuals’ sense of self and their relationships with others.…”
Section: Emotional Contagion and Self-representation In A Social Contextmentioning
confidence: 99%
“…Furthermore, emotional contagion goes beyond mere mimicry. It involves a deeper level of self-involvement, where individuals share feelings with others, even for brief moments, strengthening their emotional connection ( Mariadhas, 2019 ; Mayo et al, 2023 ). This shared emotional experience can have great effects on individuals’ sense of self and their relationships with others.…”
Section: Emotional Contagion and Self-representation In A Social Contextmentioning
confidence: 99%
“…EC is the automatic tendency to catch another's emotions (Hatfield et al, 1992;Hatfield et al, 1993;Mayo et al, 2022) and can be manifested as a demonstration of similar postural, vocal, or facial expression or as similar neurophysiological or neurological patterns of activity (Barsade 2002;Barsade, Coutifaris & Pillemer, 2018;Hatfield, Bensman, Thorton & Rapson, 2014;Hatfield et al, 1994;Hatfield, Raspon & Le, 2009;Schoenewolf, 1990;). EC is related to empathy, attunement, and bonding (Decety and Ickles, 2009;Hatfield et al, 1994;Hatfield et al, 2011;Neves et al, 2018;Spoors & Kelly, 2004), as well as to stress (Feldman & Kaal, 2007), and has been suggested to facilitate social interactions (Butler, 2011;Hatfield, Cacioppo, & Rapson, 1994).…”
Section: Autonomic Space Modelmentioning
confidence: 99%
“…Associations between EC and physiological synchrony had been suggested and demonstrated many times (Codrons et al, 2014;Dimitroff et al, 2017;Feldman, 2012;Feldman et al, 2011;Ferrer & Helm, 2013;Helm et al, 2014;Jaimovich, 2010;Karvonen et al, 2016;Liu et al, 2013;Mayo & Gordon, 2020;Mayo et al, 2022;Papp et al, 2009;Papp et al, 2013;Park et al, 2019;Saxbe & Repetti, 2010;Waters et al, 2017;Waters et al, 2014), yet the connection between EC as a trait and baseline physiological markers of the ANS remain largely unknown.…”
Section: Autonomic Space Modelmentioning
confidence: 99%
“…EC is the automatic tendency to catch another's emotions (Hatfield et al, 1992 , 1993 ; Mayo et al, 2023 ) and can be manifested as a demonstration of similar postural, vocal, or facial expression or as similar neurophysiological or neurological patterns of activity (Schoenewolf, 1990 ; Hatfield et al, 1994 , 2009 , 2014 ; Barsade, 2002 ; Barsade et al, 2018 ). EC is related to empathy, attunement, and bonding (Hatfield et al, 1994 , 2011 ; Spoor and Kelly, 2004 ; Decety and Ickles, 2009 ; Neves et al, 2018 ), as well as to stress (Feldman and Kaal, 2007 ), and has been suggested to facilitate social interactions (Hatfield et al, 1994 ; Butler, 2011 ).…”
Section: Introductionmentioning
confidence: 99%